2015
DOI: 10.3899/jrheum.150316
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Atherosclerosis Is Not Accelerated in Patients with Ankylosing Spondylitis with Low Disease Activity: New Data and Metaanalysis of Published Studies

Abstract: Low AS disease activity is not associated with accelerated atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 44 publications
5
37
5
1
Order By: Relevance
“…The authors suggested that subclinical atherosclerosis was not accelerated in patients with AS with low disease activity but reported that active AS was associated with an increase in carotid IMT values. 16 In the present study, the mean IMT of patients with AS whose BASDAI scores were 4 and above was substantially higher than the mean IMT of patients whose BASDAI scores were lower than 4.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The authors suggested that subclinical atherosclerosis was not accelerated in patients with AS with low disease activity but reported that active AS was associated with an increase in carotid IMT values. 16 In the present study, the mean IMT of patients with AS whose BASDAI scores were 4 and above was substantially higher than the mean IMT of patients whose BASDAI scores were lower than 4.…”
Section: Discussioncontrasting
confidence: 57%
“…The Clinical Trials Ethics Committee approved this study (Approval No. 16.01.17/34/23), and this study was conducted in accordance with the principles of the Declaration of Helsinki. Each participant provided a written informed consent.…”
Section: Study Group and Clinical Assessmentmentioning
confidence: 99%
“…Basal flow was increased only in reference to TNFi treatment which may be attributed to a greater potency of this factor than disease activity itself. Reversibility of these microvascular changes with clinically effective therapies show that such improvement is aligned with the fact that low disease activity or TNFi therapy reduce inherent CVD risk 34 and atherosclerosis progression in AS 35,36 . Although LDF and PORH are considered valuable tools to study microcirculation function 16,33 , they have some disadvantages such as indirect blood flow measurement and lack of standardization.…”
Section: Discussionmentioning
confidence: 94%
“…Despite this expectation, inconsistent results have been achieved in clinical trials in patients with AS. Some have reported no difference between patients with AS and controls with respect to aortic stiffness as measured with PWV (13,14,24). On the other hand, Avram et al (25) reported higher PWV in patients with AS than those in controls, as well as an association between arterial stiffness and disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Of these biomarkers, carotid intima-media thickness (CIMT) and pulse wave velocity (PWV) have been suggested as independent risk factors for future CVD (5,6). However, inconsistent results have been reported regarding the value of CIMT and PWV in the detection of subclinical atherosclerotic CVD in patients with AS (7)(8)(9)(10)(11)(12)(13)(14)(15). In a recent meta-analysis, increased risk of subclinical atherosclerosis based on increased values of CIMT and PWV has been reported (16).…”
Section: Introductionmentioning
confidence: 99%